Implementation of the Tahfidz Program at Madrasah Tsanawiyah Tahfidzul Qur’an Al-Rasyid Kartasura - Jamaludin Al Husseiny; H.M.J. Nashir; Lailla Hidayatul Amin (Edumaspul: Jurnal Pendidikan, 2024)
The aim of this research is to determine the implementation of the tahfizh al-Qur'an program at Madrasah Tsanawiyah Tahfidzul Qur'an (MTs TQ) Al-Rasyid as well as the supporting and inhibiting factors in implementing the tahfizh al-Qur'an program at the school. This research uses a qualitative approach, with a case study approach at Madrasah Tsanawiyah Tahfidzul Qur'an (MTs TQ) Al-Rasyid. The data obtained in this research was through observation, interviews and documentation studies. Based on the data obtained, the researcher used descriptive analysis, namely by describing or illustrating the findings in the field regarding the implementation of the tahfidz al-Qur'an program at the Al-Rasyid Tsanawiyah Tahfidzul Qur'an Madrasah (MTs TQ). The research results show that the tahfizh al-Qur'an program at MTs TQ Al Rasyid succeeded in creating a conducive learning environment through full support from the school, competent teachers, adequate facilities, and a personalized learning approach. Despite obstacles such as the quality of previous Al-Qur'an learning and a lack of cooperation from the dormitory chaplain, this program was able to have a positive impact on students' spiritual and academic development. Careful planning, effective implementation, and continuous evaluation ensure that each student achieves their memorization targets well, making this tahfizh program a successful educational model that is beneficial for the student's future.